Misunderstandings False Beliefs in Communication - Weizsäcker, Georg (Open Book Publishers, 2023)
What do we expect when we say something to someone, and what do they expect when they hear it? When is a conversation successful? The book considers a wide set of two-person conversations, and a bit of game theory, to show how conversational statements and their interpretations are governed by beliefs. Thinking about beliefs is suitable for communication analysis because beliefs are well-defined and measurable, allowing to differentiate between successful understandings and their less successful counterparts: misunderstandings. The book describes the theoretical framework and empirical measurements of misunderstandings - written by an economist, but in simple words and using interdisciplinary concepts. The material will benefit students and researchers of behavioural economics and its neighbouring fields, and anyone interested in human language.